Quantitative Assessment of Mutant Allele Burden in Solid Tumors by Semiconductor-Based Next-Generation Sequencing. Issue 4 (1st April 2014) - Portier, Bryce P.; Kanagal-Shamanna, Rashmi; Luthra, Rajyalakshmi; Singh, Rajesh; Routbort, Mark J.; Handal, Brian; Reddy, Neelima; Barkoh, Bedia A.; Zuo, Zhuang; Medeiros, L. Jeffrey; Aldape, Kenneth; Patel, Keyur P.
Abstract: Objectives: Identification of tumor-specific somatic mutations has had a significant impact on both disease diagnosis and therapy selection. The ability of next-generation sequencing (NGS) to provide a quantitative assessment of mutant allele burden, in numerous target genes in a single assay, provides a significant advantage over conventional qualitative genotyping platforms. Methods: We assessed the quantitative capability of NGS and a primer extension–based matrix-assisted laser desorption ionization–time-of-flight (PE-MALDI) assay and directly correlated NGS mutant allele burden determination to morphologic assessment of tumor percentage in H&E-stained slides. Results: Our results show a 100% concordance between NGS and PE-MALDI in mutant allele detection and a significant correlation between NGS and PE-MALDI for determining mutant allele burden when mutant allele burden is 10% or more. Conclusions: NGS-based mutation screening provides a quantitative assessment comparable to that of PE-MALDI. In addition, NGS also allows for a high degree of multiplexing and uses nanogram quantities of DNA, thereby preserving precious material for future analysis. Furthermore, this study provides evidence that H&E-based morphologic assessment of tumor burden does not correlate to actual tumor mutant allele burden frequency.